Absorption and Metabolism Characteristics of Rutin in Caco-2 Cells. (2nd October 2013) - Zhang, Xiaofang; Song, Jinhui; Shi, Xiaopeng; Miao, Shan; Li, Yan; Wen, Aidong
Abstract : The intestinal absorption and metabolism characteristics of the potentially beneficial polyphenol rutin were studied by measuring the intracellular accumulation and transport of rutin into Caco-2 cells with the sensitive and reliable analytical method of HPLC-coupled tandem mass spectrometry. Rutin and glucuronidated rutin were absorbed differently by the basolateral and apical membranes, and rutin showed differential permeability through the apical and basolateral sides. Approximately 33% of the rutin was metabolized to glucuronidated rutin, and the intracellular concentration of glucuronidated rutin was much lower than that of parent rutin. P-glycoprotein and multidrug-resistant proteins 2 and 3 were involved in the transmembrane transport and intracellular accumulation of rutin by Caco-2 cells. These results suggest that a specific transport system mediates rutin movement across the apical membrane in Caco-2 cells and that metabolic enzymes are important for this process.